2019
DOI: 10.21273/hortsci13690-18
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response of Winter Squash to Irrigation Regime and Planting Density

Abstract: Consumers are increasingly interested in buying local vegetables in the fall and winter. Winter squash is an important vegetable crop for local and regional fall and winter markets, and consumers are increasingly seeking high-culinary value Cucurbita maxima types such as kabocha and buttercup. Although consumer demand for kabocha and buttercup squash is increasing, Oregon farmers report they are marginally profitable. The goals of this project were 1) to identify productive k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…'Early Girl' tomato is reported to have a fruit weight of 1/4 to 3/8 lb and 'North Georgia Candy Roaster' winter squash is reported to have a fruit weight of 8 to 15 lb (Johnny's Selected Seeds). Previous work found that dry-farmed winter squash fruit weight was smaller than irrigated winter squash fruit weight during the hot and dry 2017 growing season; however, in the cool and humid 2016 growing season, there was little difference (Wetzel and Stone 2019). Tomato average fruit weight across all sites decreased over the course of the growing season, probably resulting from decreasing water availability (Giardini et al 1985).…”
Section: Mean (Se) Imentioning
confidence: 80%
See 2 more Smart Citations
“…'Early Girl' tomato is reported to have a fruit weight of 1/4 to 3/8 lb and 'North Georgia Candy Roaster' winter squash is reported to have a fruit weight of 8 to 15 lb (Johnny's Selected Seeds). Previous work found that dry-farmed winter squash fruit weight was smaller than irrigated winter squash fruit weight during the hot and dry 2017 growing season; however, in the cool and humid 2016 growing season, there was little difference (Wetzel and Stone 2019). Tomato average fruit weight across all sites decreased over the course of the growing season, probably resulting from decreasing water availability (Giardini et al 1985).…”
Section: Mean (Se) Imentioning
confidence: 80%
“…There was no effect of planting density on average fruit weight for tomato or winter squash. This contradicts Wetzel and Stone (2019), who found that the dry farm winter squash yield was unaffected by planting The dash-dotted line represents the conditional mean for the linear regressions for 2018 and the dotted line represents that for 2019. The dashed line represents the conditional mean for the linear regression for both years.…”
Section: Mean (Se) Imentioning
confidence: 81%
See 1 more Smart Citation
“…The maximum number of fruits plant -1 (4.67) was obtained from S 3 (1m × 1.5m) while S 1 (0.8m × 1m) gave minimum number of fruits plant -1 (3.76). Wetzel and Stone (2019) who reported higher fruit number with lower population density. The highest individual fruit weight (1.36 kg) was found from S 3 while the lowest individual fruit weight (1.16 kg) was found from S 2 (1m × 1m).…”
Section: Effect Of Plant Spacingmentioning
confidence: 96%
“…With the continuous development of the economy and technology, the influence of human social activities is increasing. In addition to temperature, precipitation, and dry and wet conditions, there are also different drip irrigation modes [45], mulching conditions [46], planting densities [47], balanced fertilizers such as nitrogen and phosphorus [48], adaptabilities of maize itself to the environment, and crop management methods, which all affect the yield of maize. Therefore, a multi-factor evaluation model that can be used to evaluate climate variables and their impact on yield remains to be constructed.…”
mentioning
confidence: 99%